2001
DOI: 10.1186/1751-0147-42-271
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcium Response Following Oral Zinc Oxide Administrations in Dairy Cows

Abstract: Six non-pregnant cows were allocated into 3 groups. Group 1 comprised a pair of lactating cows, whereas groups 2 and 3 each comprised a pair of non-lactating cows. The cows in groups 1 and 2 were dosed intraruminally by stomach tube with zinc oxide at 120 mg Zn per kg of bodyweight at weekly intervals for a period of 33 days. Each cow received a total of 4 doses of zinc oxide. Group 3 served as non-treated control group. Blood samples were collected from all 6 cows daily. Serum was analysed for concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Unfortunately, at this time, the genetic and hormonal machinery systems for Ca homeostasis are switched off, and need some time to be activated. Similar results were recorded before in a study performed by Houe et al [19], where the incidence rate of hypocalcaemia in individual herds reached up to 34%, with average of 5 -10% of individual cows. Moreover, Roche [20] reported that the incidence of subclinical hypocalcaemia was 33% in grazing New Zealand dairy cows, while the incidence of clinical hypocalcemia was 5 % only.…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, at this time, the genetic and hormonal machinery systems for Ca homeostasis are switched off, and need some time to be activated. Similar results were recorded before in a study performed by Houe et al [19], where the incidence rate of hypocalcaemia in individual herds reached up to 34%, with average of 5 -10% of individual cows. Moreover, Roche [20] reported that the incidence of subclinical hypocalcaemia was 33% in grazing New Zealand dairy cows, while the incidence of clinical hypocalcemia was 5 % only.…”
Section: Discussionsupporting
confidence: 91%
“…In the same manner; Amara et al (2015) showed that sub-acute ZnNPs dose resulted in a significant decrease of Ca 2+ ions level in brain homogenate. Also, Thilsing and Jorgensen (2001) indicated the antagonism between Ca 2+ and Zn 2+ in dairy cows after zinc oxide gavage. Sruthi et al (2018) revealed that ZnNPs treatment induced a significant Ca 2+ ions level reduction in brain tissue.…”
Section: Discussionmentioning
confidence: 97%
“…The objective of these experiments was to reduce the bioavailability of dietary Ca in the gastrointestinal tract by the administration of synthetic zeolite A, based on the evidence that one of the best ways to prevent milk fever is to feed cows with low calcium diets during the dry period [83][84][85][86][87]. The results obtained were satisfactory as the administration of synthetic zeolite A, either as an oral drench or supplemented to the total mixed ration, during the dry period reduced the bioavailability of dietary Ca and efficiently protected against milk fever, by stimulating Ca-homeostatic mechanisms prior to parturition [88][89][90][91][92][93]. Furthermore, Thilsing-Hansen et al [92] proposed that the best ratio zeolite/Ca for the prevention of milk fever was 10-20 and that zeolite had the same efficiency either administrated for the last 4 or 2 weeks of the dry period.…”
Section: Milk Fevermentioning
confidence: 99%
“…The results obtained were satisfactory as the administration of synthetic zeolite A, either as an oral drench or supplemented to the total mixed ration, during the dry period reduced the bioavailability of dietary Ca and efficiently protected against milk fever, by stimulating Ca-homeostatic mechanisms prior to parturition [88][89][90][91][92][93]. Furthermore, Thilsing-Hansen et al [92] proposed that the best ratio zeolite/Ca for the prevention of milk fever was 10-20 and that zeolite had the same efficiency either administrated for the last 4 or 2 weeks of the dry period.…”
Section: Milk Fevermentioning
confidence: 99%